Choice Of National Strategy And Industrial Organization Comparing Airframe Production Between Brazil And Japan - Kanatsu, Takashi (Penerbit Universiti Sains Malaysia (USM Press), 2006)
This paper examines two reasons why the development of airframes as a national aircraft industry1 have been met with more success in Brazil than in Japan: First, Brazil's aircraft industry was nurtured by a unified government administrative structure while in Japan the same industry instead became a victim of inter-ministerial battles. Second, the Brazilian government nurtured a single specialized national-champion firm, Embraer (Empresa Brasileira de Aeronáutica S.A.)2, while the Japanese government relied on the traditional consortium approach that epitomizes most Japanese postWorld War II industrial ventures. While usually successful, the consortium approach did not do as well to build a domestic aircraft industry in Japan. Making airplanes turned out to be an exception in Japanese business partly also because of the involvement of several government agencies at varying levels. In other Japanese industries, such as steel, semiconductors, and computers, a single ministry, the Ministry of International Trade and Industries (MITI) had managed these consortiums relatively successfully.